Relación de la calidad de vida en salud y molestias músculo esqueléticas en trabajadores de una empresa de comercialización de materiales de construcción de la ciudad de Lima 2019 - Bazán Ponte, Yanina (2019)
The present research work became a company of construction materials sector of the city of Lima in the year 2017-2018, its main objectives were the relationship between quality of life and musculoskeletal complaints, determine the Test exam of the CMDQ questionnaire (Cornell Musculoskeletal Disorders Questionnaires). The study was carried out in 2 stages. The first stage consisted in carrying out the validation of the CMDQ questionnaire. In the second stage, 2 questionnaires were applied to the CMDQ - YBP after validation and the Quality of Life in Health Questionnaire and Validation in 2012. The study design was non-experimental quantitative applied to 146 workers in the commercial sector of the city of Lima. The validity of the content, the criterion, the internal consistency and the reliability of the examination was demonstrated, resulting in a CMDQ instrument in companies in the commercialization sector. The greatest incidence of discomfort in the skeletal muscle and in the workers is reduced in time (44.8%), in the upper back (33.3%), in the lower back (26.7%) and in the workers they are used in the main rows ( 44.4%), hip and buttocks (20%), and high backs with (15.6%). The results correspond to the quality of life are related to health in its component of physical health was shown that 90% presents the good quality of life in health and only 10% shows poor quality of life In the health. In the mental health component, the vast majority of workers present and have a good.